Cyclic Behavior of Different Connections in Precast Concrete Shear Walls: Experimental and Analytical Investigations - Yooprasertchai, Ekkachai; Wiwatrojanagul, Pongsak; Saingam, Panumas; Khan, Kaffayatullah (My University, 2023)
This study investigated the grouted sleeve splices and corrugated duct splices between shear walls and footing. In this regard, three shear walls were experimentally tested. One wall was cast monolithically with the foundation (RCWS), whereas two walls were precast. One wall was connected to the foundation using splice sleeves (PGWS), and another with corrugated duct splices (PCWS). All the walls were tested under reverse cyclic loading and a constant axial load. It was observed that the performance of specimen PGWS was controlled by rocking, and a premature connection loss was observed at one of the grouted sleeve splices. The hysteretic performance of specimen PCWS was close to that of specimen RCWS, whereas extensive pinching was observed in the hysteretic response of specimen PGWS. The peak load, ductility, secant stiffness, and energy dissipation of specimens RCWS and PCWS were in good agreement, whereas the energy dissipated by specimen PGWS was considerably lower than the corresponding values of specimens RCWS and PCWS. Nonlinear fiber-based modeling in OpenSees was performed using SFI-MVLEM elements. The predicted hysteretic response of the OpenSees model was in close agreement with the experimental response.
Keywords: connections; corrugated duct; cyclic loading; OpenSees; precast concrete; shear wall